La Révolution française et la gauche allemande dans le premier XIXe siècle : les cas de Ludwig Börne et Bruno Bauer - Stéphanie Roza (Astérion)
The comments on the French Revolution by the young Marx and Engels are well-known and have been abundantly discussed. However, what is less known is that they belonged to a generation of German intellectual activists who, in the 1830s and 1840s, constantly used the French Enlightenment as a key reference to assess contemporary German philosophy and political life. This article provides an analysis of the two diverging positions on such questions articulated by two representatives of this generation: Ludwig Börne who elaborated a German version of Jacobinism, and Bruno Bauer, a young Hegelian who promoted a German philosophical revolution whose radicalism and spiritual depth was capable of surpassing that of the French Revolution. Thus, as underlined by Lucien Calvié, the relationship of German intellectuals to the French Revolution during the Vormärz (pre-March) appears as an ambiguous one: just as the fox with the grapes in La Fontaine’s fable, left-wing Germans viewed revolutionary France with a mixture of envy and frustration.